Double suicide in Japan in the post-war reconstruction period, with reference to contemporary Japan. (July 2023) - Satoh, Fumiko; Nagato, Junpei; Irie, Wataru; Sasaki, Chizuko; Ochiai, Eriko; Kondo, Maho; Hayashi, Kino
After Japan's post-war reconstruction, in the early 1950s, cases of double suicide, in which two people (particularly young lovers) leave a suicide note and die together, were a relatively frequent occurrence. During the three-year period between 1954 and 1956, 5466 suicides were recorded in the special wards of Tokyo, including 79 cases of double suicides, accounting for 158 deaths. In these double suicide cases (2.89% of all deaths by suicide), the evidence revealed that 65.8% involved lovers and 29.1% involved married couples. By contrast, contemporary data indicate a large drop in suicide pacts between lovers to 15.9% and an increase between spouses to 48.8%. Conceivably, the relatively high double-suicide rate after post-war reconstruction reflected difficulties for the younger generation in reconciling 'marriage based primarily on love' and the traditional family system, specifically marriage problems and stress caused by rapidly changing post-war values. One notable difference between victims of double suicide in 1954–1956 and the contemporary period is the younger average age of the former. Another important shift was found in the most common causes of death among victims of double suicide: in 1954–1956 these were poisoning by cyanide or hypnotic drugs, compared to carbon monoxide poisoning and hanging in modern times. We discuss similarities and differences concerning double suicides in relation to social and economic conditions in Japan in the 1950s and today.